Distal urethral carcinoma: Contemporary management with phallus preserving techniques. Issue 5 (October 2022) - O'Kelly, J.A.; Browne, E.; Murray, P.; Keane, J.; Daly, P.; Cullen, I.M.
Abstract: Introduction: Primary urethral carcinoma is a rare clinical entity with an incidence of 1 case per million in the United Kingdom. Cancers of the distal urethra are most commonly of squamous subtype and often associated with Human Papilloma Virus infection. Penile preserving techniques are recommended in tumours of the pendulous urethra with a number of surgical approaches described. Herein, we describe the surgical management of 7 patients presenting with primary urethral carcinoma. Methods: Seven patients diagnosed with primary urethral carcinoma of the distal urethra were identified using a prospectively maintained penile cancer database at our institution from May 2017 to November 2020. Results: The mean age at presentation was 56.5 (33-80) years. Presenting symptoms included visible lesion, LUTS and a groin mass. Three patients had lesions located within the glanular urethra and had a distal urethrectomy and primary closure. Two patients with lesions extending proximal to the glanular urethra and into or beyond the fossa navicularis had a distal urethrectomy with a hypospadic neomeatus formation. One patient with tumour extending into the glans penis underwent distal urethrectomy and partial glansectomy with split thickness skin graft. A partial penectomy was performed for one patient with urethral tumour invading the corporal heads. Mean follow-up was 23.4 (±17.0) months. There have been no disease recurrences to date. Conclusion: Penile preserving techniques are feasible in patients with tumours of the pendulous urethra and do not appear to compromise local control. Highlights: Primary urethral cancer is a rare clinical entity (1 per million in United Kingdom). Distal urethral cancers are more commonly squamous type. Theses tumours are histologically similar to those of the glans penis and prepuce. Risk factors include urethral strictures, BXO and HPV infection. Phallus preserving techniques are recommended when feasible.